Impact of left atrial appendage morphology on thrombus formation after successful left atrial appendage occlusion: assessment with cardiac-computed-tomography - Dieker, Wulf; Behnes, Michael; Fastner, Christian; Sartorius, Benjamin; Wenke, Annika; Gill, Ishar-Singh; El-Battrawy, Ibrahim; Kuschyk, Jürgen; Papavassiliu, Theano; Hoffmann, Ursula; Schönberg, Stefan; Borggrefe, Martin; et al. (Scientific reports, 2018)
A standardized imaging algorithm by cardiac computed tomography angiography (cCTA) (LOVE-view) was used in 30 patients to evaluate the influence of different left atrial appendage (LAA) morphologies on development of thrombosis in the LAA 6 months after implantation of an occlusion device (Watchman or Amplatzer-Cardiac-Plug) in patients with non-valvular atrial fibrillation, CHA2DS2-VASc-Score >1 and a contraindication for oral anticoagulation. The distribution of different LAA morphologies was 40% windsock, 17% broccoli and 43% chicken wing type. There was no significant difference in the level of thrombosis regarding LAA morphology or the type of chosen occlusion device. The rates of complete LAA thrombosis was 40% in broccoli type, 33% in windsock and 15% in chicken wing type. Independently of LAA type, 13% had none and 60% incomplete thrombosis. The ratio of density (LA/LAA) was 0.14 in patients with complete thrombosis and 0.67 in those with none or incomplete thrombosis. cCTA and the LOVE-view-imaging-algorithm were shown to be a valuable method for standardized imaging in clinical routine in a greater set of patients. Surprisingly thrombosis of the occluded LAA was still in progress in most cases at 6 months, whereas further studies are needed defining its clinical consequences, especially for the selection of the optimal post-procedural antithrombotic treatment strategy.
Gesehen am 03.09.2019